2023
DOI: 10.1088/1681-7575/acee82
|View full text |Cite
|
Sign up to set email alerts
|

Phase shifting angle interferometer

B J Eves,
I D Leroux,
A J Cen

Abstract: A phase shifting Twymann-Green interferometer for the measurement of plane angle has been developed and characterized using a small-angle generator directly traceable to the definition of the radian. The impact of surface form on the measured angle was explored using a simple deformable mirror. The angle sensitivity of the interferometer did not depend upon the surface form. Comparison of the calibrations of two polygons and two angle gauge blocks by both the angle interferometer and a commercial autocollimato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Given detailed knowledge of the surface form, one could correct for these measurand differences rather than expanding uncertainties to cover them. Such information is most easily obtained using an interferometer and NRC recently built a PSI specifically to measure both surface form and plane angle [10]. We have found that it has a lower plane angle measurement uncertainty (ignoring measurand differences) than our autocollimator.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given detailed knowledge of the surface form, one could correct for these measurand differences rather than expanding uncertainties to cover them. Such information is most easily obtained using an interferometer and NRC recently built a PSI specifically to measure both surface form and plane angle [10]. We have found that it has a lower plane angle measurement uncertainty (ignoring measurand differences) than our autocollimator.…”
Section: Discussionmentioning
confidence: 99%
“…As the surface deforms, the different choices of f lead to differences in reported angle on the scale of arcseconds. The x-axis angles are more sensitive to the choice of f than the y-axis angles, because the symmetry of our mirror mount leads to a deformation roughly symmetric about a horizontal line [10]. The mirror angle distribution ρ M therefore roughly symmetric for y but markedly asymmetric in x.…”
Section: Symbolmentioning
confidence: 96%
See 1 more Smart Citation
“…This method of measuring the phase is generally more accurate, but the corresponding set of equipment is also more expensive and complex. This method generally has a small range but high accuracy [ 6 , 9 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ], and in order to further investigate its mechanism and error correction, an independently characterized angle measurement system that is useful for angle calibrations is proposed [ 113 ]. As for the environmental effect, measurement sensitivity can be improved through immersing the beta-barium borate plate in grapeseed oil, which can avoid deliquescence in humidity [ 114 ].…”
Section: High-precision With Single Axismentioning
confidence: 99%